2005
DOI: 10.2134/agronj2005.0118
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐Offs in Forage and Seed Parameters of Annual Medicago and Trifolium Species in North‐Central Texas as Affected by Harvest Intensity

Abstract: value and seed production is likewise affected by climate and soil (Cocks, 1995). The trade-off between early spring harvest of cool-season annualMore information is needed, however, on the approforage legumes and summer seed production may shed light on subsepriate management of naturalized and cultivated annual quent yearly stand regeneration. Sixteen annual clover and medic cullegume stands. Although seed production is essential tivars or locally collected accessions were seeded in the autumn of for stand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
22
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 20 publications
7
22
4
Order By: Relevance
“…The results showed, however, that establishment of an apparently satisfactory plant stand did not necessarily result in significant production of legume. Warm-and cool-season legume yields were lower than reported in other work (Davis et al, 1994;Rao and Phillips, 1999;Rumbaugh and Johnson, 1986;Muir et al, 2005). Some yield limitation may be attributed to the low productivity of the experimental site that is typical of unimproved mixed grass pasture in the SGP (Berg, 1995;Gillen and Berg, 1998), but the use of a no-till management regime in the work reported here is also likely to have reduced legume production.…”
Section: Forage Nitrogen Concentration and Yieldcontrasting
confidence: 56%
See 1 more Smart Citation
“…The results showed, however, that establishment of an apparently satisfactory plant stand did not necessarily result in significant production of legume. Warm-and cool-season legume yields were lower than reported in other work (Davis et al, 1994;Rao and Phillips, 1999;Rumbaugh and Johnson, 1986;Muir et al, 2005). Some yield limitation may be attributed to the low productivity of the experimental site that is typical of unimproved mixed grass pasture in the SGP (Berg, 1995;Gillen and Berg, 1998), but the use of a no-till management regime in the work reported here is also likely to have reduced legume production.…”
Section: Forage Nitrogen Concentration and Yieldcontrasting
confidence: 56%
“…The poor self-seeding performance of hairy vetch reflects results reported by Volesky et al (1996), but black medic has reported capacity for regeneration by self-seeding (Rumbaugh and Johnson, 1986) and is noted for the persistence of its seedbank (Pavone and Reader, 1982). However, recent work has also reported poor reseeding and low forage production by George black medic in the SGP (Muir et al, 2005) and these authors showed that a local ecotype of black medic could be significantly more productive of both seed and forage than George. Self-seeding of lespedeza was also variable and further demonstrates the uncertainty of dependence on regeneration of a companion legume by self-seeding.…”
Section: Forage Nitrogen Concentration and Yieldmentioning
confidence: 81%
“…This is particularly true on soils that are low in P, such as those that occur in much of north-central Texas and south-central Oklahoma (National Soil Survey Center, 2004). Windthorst (fine, mixed thermic Udic Paleustalf) fine sandy loam soils can be particularly low in plant-available P (Muir et al, 2001(Muir et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…(Ocumpaugh et al, 1997). Plantings of Devine little burr medic made in the area around San Antonio area and northward consistently produce as much or more than other available medics (Muir et al, 2005). Devine typically produces forage later in the season than Armadillo.…”
mentioning
confidence: 99%
“…Devine out‐produced several legumes in May harvests in 2004, to contribute to this superiority over other medics in the test. In north Texas, Devine will produce more forage than Armadillo, except in wet and mild winters, as Armadillo will winter kill in the cold winters in north Texas (Muir et al, 2005).…”
mentioning
confidence: 99%